Comparative evaluation of periodontal inflammatory conditions among gutka-chewers with and without prediabetes - Puneet Bhardwaj; Zoya Chowdhary; Vandana Sharma; Ravi Ladani; Sonamben Kishorchandra Modi; Sudhanshu Bhardwaj; Kasper D Hundal (Wolters Kluwer Medknow Publications, 2021)
Background: The metabolic syndrome has become one of the major public-health challenges worldwide which include diabetes, prediabetes (raised blood glucose level), abdominal obesity, high cholesterol level, and high blood pressure. Periodontitis is described as a multi-factorial irreversible and cumulative condition and, is also the sixth complication of diabetes. Areca nut chewing has already been linked with the development of various cancers, and more recently with metabolic syndrome. Therefore, the purpose of the study is to investigate the association of periodontal inflammatory conditions among gutka chewing with and without prediabetes patients. Materials and Methods: There are about 50 pre-diabetic and 50 healthy patients, both males and females with the age range of 18 years to 45 years, were included in the study. They were then divided into 4 groups based upon gutka chewers and non-chewers i.e., pre-diabetic gutka chewers (PDC), pre-diabetic non-chewers (PDNC), healthy gutka chewers (HC), and healthy non-chewers (HNC). A complete demographic data was obtained along with clinical and radiographic parameters i.e. plaque index (PI), sulcus bleeding index (SBI), probing depth (PD), marginal bone loss (MBL) were recorded. A statistical analysis was performed and Bonferroni adjustment post hoc test was performed for multiple comparisons. Results: The overall results suggested that the clinical periodontal parameters i.e., PD, PI, SBI and radiologic parameters i.e., MBL are significantly higher in prediabetes chewers compared with healthy chewers and healthy non chewers. Conclusion: The periodontal inflammatory conditions are worse in gutka chewers compared to non-chewers in healthy and pre-diabetic patients, concluding that the severity of periodontal inflammation is governed by hyperglycemia when compared to habitual gutka usage.